(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
The implementation of physical education and health learning is taught to develop children’s motor skills. This study aims to analyze the effect of implementing the ABC Running Drill on the improvement of gross motor skills in elementary school students. The method used is an experiment with a pre-experimental design of One Group Pretest-Posttest. The research sample consisted of 25 students from SDN Babakan Jampang 1 with an age range of 9-10 years. The instrument used is the Test of Gross Motor Development 2nd Edition (TGMD-2). Data were analyzed using normality tests, homogeneity tests, paired sample t-tests, and R-Square tests with the help of SPSS 27. The research results show that the ABC Running Drill has a significant effect on the improvement of students’ gross motor skills with a Sig. (2-tailed) value of 0.001 < 0.05 and an R-Square value of 0.610, which means 61% of the variation in the improvement of gross motor skills is explained by this exercise. In conclusion, the ABC Running Drill is effective in improving the gross motor skills of elementary school students.